Analysis of nonlinear dynamic responses for functionally graded beams resting on tensionless elastic foundation under thermal shock. (10th May 2016) - Zhong, Jun; Fu, Yiming; Chen, Yang; Li, Yingli
Abstract: This paper investigates the nonlinear transient thermal responses of functionally graded beams resting on tensionless foundation under unsteady heat conduction. The interaction between functionally graded beams and tensionless foundation is only compressive without tensile reaction. The whole model is established based on Euler beam theory and solved by the combination of differential quadrature method (DQM), Newmark method and Newton–Raphson method. Some detailed numerical results are carried out to reveal the transient heat conduction procedure and the mechanical behaviors of functionally graded beam resting on tensionless foundation.